2004
DOI: 10.1021/jp0401776
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical, Structural, Vibrational, NMR, and Thermal Evidence of the Inter- versus Intramolecular Hydrogen Bonding in Oxamides and Thiooxamides

Abstract: This contribution describes the study of hydrogen bonding in secondary oxamides, monothiooxamides, and dithiooxamides by ab initio calculations, X-ray diffractions, NMR spectra, thermal analysis, and variabletemperature infrared and Raman spectroscopy. The results can all be interpreted as a function of the change in the strength and the nature of the hydrogen bonding by substituting oxygen for sulfur in the series CH 3 -HNCOCONHCH 3 , CH 3 HNCSCONHCH 3 , CH 3 HNCSCSNHCH 3 and by changing the steric influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
6
20
0
1
Order By: Relevance
“…Experimental and theoretical studies have demonstrated that intramolecular hydrogen bonds in oxalamides determine their geometry and conformation whereas intermolecular hydrogen bonds increase their stability. [1][2][3] Due to these interactions, oxalamides are applied in diverse areas such as artificial receptors for biological recognition, 4 in engineering and crystal design 5 and in organogels formation. 6 Recently, oxalamide derivatives were identified as HIV-1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical studies have demonstrated that intramolecular hydrogen bonds in oxalamides determine their geometry and conformation whereas intermolecular hydrogen bonds increase their stability. [1][2][3] Due to these interactions, oxalamides are applied in diverse areas such as artificial receptors for biological recognition, 4 in engineering and crystal design 5 and in organogels formation. 6 Recently, oxalamide derivatives were identified as HIV-1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of the oxalamide group to form intramolecular hydrogen bonds has been confirmed by spectroscopic methods like NMR and also X-ray diffraction 95,[97][98][99][100][101] .…”
Section: Conformation and Hydrogen Bonding Of Oxalamidesmentioning
confidence: 91%
“…This clearly indicates that the hydrogen bonds are bifurcated exhibiting weak intramolecular and stronger intermolecular hydrogen bonds. Moreover, infrared spectra of oxalamides dissolved in CH 2 Cl 2 at high dilution revealed the presence of hydrogen bonds indicating intramolecular hydrogen bonding 98 . The intra-and intermolecular hydrogen bond interactions also depend highly on substituents.…”
Section: Conformation and Hydrogen Bonding Of Oxalamidesmentioning
confidence: 99%
See 2 more Smart Citations